Young brazilians and their preference for Sciences discipline (Research, Society and Development, 2021)
The ROSE project (The Relevance of Science Education) seeks to understand attitudinal and emotional data of young adults regarding the subjects Science and Technology collected from a questionnaire applied in over 40 countries. The results of ROSE-Brazil showed that while young adults have higher interest in the sciences, they like other disciplines better. This study aims to understand how young Brazilians behave in the face of this divergence around interest and preference for the science discipline. To achieve our goal, we used the raw data from the ROSE-Brazil 2011 sample and the statistical analysis methods. Young Brazilians are divided into four groups: Not-positive priority (3.98%) group has no interest in science classes, but prefers this discipline to others; Poor priority (20.26%) group has neither interest nor preference for the science discipline; Specific priority (30.6%) group is interested and prefers the science subject to others; Other priority (45.14%) is the most expressive group whose young adults are interested in the science discipline, but do not prefer it. Three of these groups are more representative of the reality of young Brazilians. For this reason, investigating the differences between the interests and habits of young people in each group linked to the subjects Science and Technology is relevant in order to help create strategies that make science teaching more attractive.